INTERNATIONAL SOCIAL STANDARDS IN THE CONTEXT OF IMPROVEMENT OF THE SOURCE SYSTEM OF SOCIAL SECURITY LAW: THE SCIENTIFICTHEORETICAL ASPECT - Melnik , O. (Київський національний університет імені Тараса Шевченка, 2019)
In this scientific article, the theoretical and legal aspects of international social standards areconsidered as an important component of the development of the system of sources of social security law.The emphasis is on key issues of the current state of sources of social welfare through the prism of acomprehensive social reform. The importance of developing qualitative approaches to the implementationof international social standards is also emphasized. The doctrinal definitions of "international socialstandards" are analyzed. Conclusions and suggestions on principles and mechanisms of implementationof international social standards in the process of development of the latest system of sources of socialsecurity law are made.

У цій науковій статті розглядаються теоретико-правові аспекти міжнародних соціальнихстандартів як важливі складові розвитку системи джерел права соціального забезпечення.Акцентується увага на ключових проблемах сучасного стану джерел права соціальногозабезпечення через призму комплексної соціальної реформи. Наголошено на важливостіформування якісних підходів до імплементації міжнародних соціальних стандартів.Проаналізовано доктринальні визначення «міжнародні соціальні стандарти». Зроблено висновкита пропозиції щодо принципів та механізмів імплементації міжнародних соціальних стандартів упроцесі розбудови новітньої системи джерел права соціального забезпечення.
МІЖНАРОДНІ СОЦІАЛЬНІ СТАНДАРТИ У КОНТЕКСТІ УДОСКОНАЛЕННЯ СИСТЕМИ ДЖЕРЕЛ ПРАВА СОЦІАЛЬНОГО ЗАБЕЗПЕЧЕННЯ: НАУКОВОТЕОРЕТИЧНИЙ АСПЕКТ
Keywords: social security; sources of social security law; UN; ILO; international legal acts; international social standards; legislation; trends in the development of sources of social security law.; соціальне забезпечення; джерела права соціального забезпечення; ООН; МОП; міжнародно-правові акти; міжнародні соціальні стандарти; законодавство; тенденції розвитку джерел права соціального забезпечення.